Functional and habitat characteristics associated with nativeness, rarity, and invasiveness in the aquatic vascular flora of Sardinia - Mauro Fois; Alba Cuena-Lombraña; Jennifer Nagel Boyd; Lina Podda; Gianluigi Bacchetta (Global Ecology and Conservation)
Mediterranean wetlands are of great conservation concern given their high biodiversity, functional value, societal importance, and significant decline during recent decades. Within the contexts of species protection and functional resilience, understanding the biological and environmental factors that influence the composition and diversity of wetland plant communities could help to inform management of these critical systems. To examine such factors, we considered 13 functional and habitat characteristics in explanatory models of the nativeness, rarity, and invasiveness of a comprehensive flora of 224 vascular plant species associated with wetlands in Sardinia. We categorised 59 of the 184 native species as rare and 21 of the 40 non-native species as invasive. Our models revealed some functional and habitat characteristics that are significantly associated with plant species’ nativeness, rarity, and invasiveness in Sardinian wetlands. Specifically, native species generally have smaller flowers than non-native species, while non-native species tend to flower later and reproduce more vegetatively. Rare native species typically occur across a narrower elevation range, have shorter flowering duration, and are less likely to reproduce vegetatively than common species, while invasive species tend to have larger flowers than non-invasive species. The relatively high incidences of rarity and invasiveness in Sardinian wetlands are likely influenced by the intrinsic fragmentation of freshwater environments and profound anthropogenic modifications in the region. In addition, we suggest that differences in reproductive traits may further contribute to species’ rarity and invasiveness in these systems.